Effects of different oxygen concentrations on the proliferation, survival, migration, and osteogenic differentiation of MC3T3-E1 cells. (4th May 2019) - Liu, Haixin; Yang, Minsheng; Wu, Guofeng; Yang, Lianjun; Cao, Yanlin; Liu, Chun; Tan, Zhiwen; Jin, Yanglei; Guo, Jiasong; Zhu, Lixin
ABSTRACT: In physiological and pathological environments, the concentration of oxygen around osteoblasts varies widely. No studies have systematically evaluated the effects of different oxygen concentrations on the proliferation, survival, migration, and osteogenic differentiation of osteoblasts. In this study, we cultured the osteoblast precursor cell line MC3T3-E1 in small individual chambers with oxygen concentrations of 1%, 3%, 6%, 9%, and 21%. Cell proliferation was evaluated by the proliferation index test and EdU staining. To test cell survival, a live/dead assay was performed. A tablet scratch assay was performed to detect the migratory ability of the cells. Bone nodule formation experiments and immunofluorescence and Western blotting analyses of osteogenic-related proteins were performed to assess the osteogenic differentiation of the cells. We found that the proliferation and osteogenic differentiation ability of MC3T3-E1 cells in different oxygen concentrations were both approximately bell-shaped curves and that the optimal oxygen concentrations were approximately 6% and 9%, respectively. The live/dead assay showed that the survival of MC3T3-E1 cells in different oxygen concentrations was affected by the amount of serum. The tablet scratch experiment showed that there was greater cell migration with oxygen concentrations of 1%, 3%, and 21% than with oxygen concentrations of 6% and 9%. Our results have significant reference value for the intervention of the pathological processes involving osteoblasts, such as fracture, osteoporosis, and some vascular diseases. These results also have an important guiding role for the new scientific idea that osteoblasts can function as treatment cells to repair bone defects.